Caracterização química e potencial antimicrobiano do mel de abelha do semiárido paraibano - Guimarães, Niedja Eloi de Sousa (2024)
Honey has been effective in treating a variety of injuries, ranging from burns to persistent wounds that do not heal. It functions as an antibacterial and antibiofilm agent, possessing both anti-inflammatory and pro-inflammatory properties, as well as offering respiratory health benefits by helping to combat asthmatic and bacterial infections. Microbial resistance has been a major challenge in global public health and a serious threat to human health in the 21st century. Due to the increasing need to combat infections caused by microorganisms resistant to existing antimicrobials, scholars have been exploring therapeutic options of natural origin with medicinal effects to apply these substances as an alternative to conventional drug therapy. The aim of this study was to chemically characterize and evaluate the biological potential of stingless bee honey produced in the semi-arid region of Paraíba at different times. Honey from the Apis mellifera bee was acquired directly from meliponiculturists in the semi-arid region of Paraíba, predominantly from flowering periods of Brazilian peppertree and quince, collected during the dry and rainy seasons. The characterization of honey was performed by analyzing pH, viscosity, Brix degree, and density. The total phenol content was determined by the Folin-Ciocalteu method. Antioxidant tests were performed using the DPPH method (2,2-diphenyl-1-picrylhydrazyl). The thermal profile of honey was determined through Thermogravimetric (TG) and Differential Thermal Analysis (DTA) techniques. The fingerprint of bee honeys was obtained using high-performance liquid chromatography (HPLC). The antibacterial potential of semi-arid region bee honeys from Paraiba was determined by agar diffusion assays and minimum inhibitory concentration/minimum bactericidal concentration (MIC/MBC) by microdilution in 96-well plates against strains of Staphylococcus aureus (ATCC 17193), Escherichia coli (ATCC 25922), and Pseudomonas aeruginosa (ATCC 27853), which are frequently associated with wound infections, burns, and respiratory diseases. All three tested microorganisms showed sensitivity to Apis mellifera honeys, with minimum inhibitory concentrations ranging from 6.25% to 14.58% against Staphylococcus aureus and from 6.25% to 20.83% against Pseudomonas aeruginosa, while for Escherichia coli, there was no variation, with a minimum inhibitory concentration of 25% for the four tested honeys. Among the four Apis mellifera honeys analyzed, honey C (Quince, rainy) showed the best antibacterial activity demonstrated against Staphylococcus aureus and Pseudomonas aeruginosa, with similar results to the others against Escherichia coli. The studied semi-arid region honeys from Paraíba demonstrated antibacterial potential and with further studies, they could be considered as an option for active pharmaceutical ingredient in the treatment of bacterial infections.